Chemical characterization and bioactivity of the most widely appreciated cultivated mushrooms: studies in fruiting bodies and mycelia - Reis, Filipa S. (2012)
Mushrooms are part of the human diet for thousands of years, and their consumption increased greatly in recent times. One of the main reasons for this increase is the combination of their nutritional value as well as for their medicinal and nutraceutical properties. The present work reports a comparative study of highly consumed fresh cultivated mushroom species worldwide: Agaricus bisporus (white and brown), Pleurotus ostreatus (oyster mushroom), Pleurotus eryngii (king oyster mushroom) and Lentinula edodes (shiitake). It was assessed the nutritional value and chemical composition of the mushrooms, and their mycelia were produced by in vitro culture to make a comparative analysis of the antioxidant activity and phenolic profile of fruiting bodies and the corresponding mycelium. L. edodes (shiitake) revealed the highest levels of macronutrients, unless proteins, as also the highest sugars, tocopherols and polyunsaturated fatty acids (PUFA) levels, and the lowest saturated fatty acids (SFA) content. Although phenolic compounds and derivatives investigated have been found in both fruiting bodies and mycelia, generally the species in vivo showed a higher antioxidant potential than the mycelium obtained by in vitro culture.